Collaborative Effort Capture Tacit Knowledge Of The Malay Shadow Puppeteers In Malaysia - Nurul Afifah Vanitha, Abdullah; Zuraidah, Abdul Manaf (-, 2014)
Show puppet performance or Wayang Kulit is among the oldest form of traditional theatre in the region of Southeast Asia. In Malaysia there are three forms of Wayang Kulit, known as Wayang Jawa, Wayang Melayu and Wayang Kelantan. Like most tradisional theatre in other parts of the world, Wayang Kulit has been identified as amongst Malaysias' performance art that is facing extinction. The number of wayang kulit groups and master puppeteers have declined drastically since the 1980s. Islamic revalation in 1980s in Malaysia is among the major factors for this situation, besides tremendous fall in the number of wayang kulit performance especially in Kelantan, an Islamist party controled state. These Islamist state government condon ritual practices that are observed by master puppeteers during wayang kulit performances, which are unfamiliar culture in Islam. Since the 1980s, the emerging numbers of young puppeteers are also not encouraging although many efforts have been carried out by the Ministry of Cultural Affairs since the 1970s. This observation muted collaborative scholarly efforts in the field of theatre and information mangement to capture, document and propose a teaching learning module of puppeteering the Malay shadow theatre. The main focus of the proposed research was to study and document the tacit knowledge and knowledge transfer of the master puppeteer to a young puppeteer in Malaysia. This paper will mainly discusses the initial scholarly efforts in preserving an endangered performance arts culture in Malaysia. The first part of this paper will focus on collaborative efforts of scholars from two different fields of study in designing the above mentioned research proposal. Meanwhile the second half will elaborate its research design. In short, this paper intends to proof that scholars should challenge themselves by crossing and merging boundaries in order to explore and contribute new knowledge to their respective field of study.